1998
DOI: 10.1093/brain/121.9.1749
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal inhibitory visual-vestibular interaction. Visual motion stimulation deactivates the parieto-insular vestibular cortex

Abstract: The vestibular system--a sensor of head accelerations--cannot detect self-motion at constant velocity and thus requires supplementary visual information. The perception of self-motion during constant velocity movement is completely dependent on visually induced vection. This can be linear vection or circular vection (CV). CV is induced by large-field visual motion stimulation during which the stationary subject perceives the moving surroundings as being stable and himself as being moved. To determine the unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
319
3
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(369 citation statements)
references
References 28 publications
41
319
3
6
Order By: Relevance
“…Under alcohol induced perceptional changes, a reciprocal inhibitory auditory-visual interaction may provide a successful way to shift the dominant sensorial weight from one modality to the other as a compensatory mechanism. A similar inverse functional correlation in sensory activations could be shown for visual-vestibular stimulations of subjects without pharmacological challenge (Wenzel et al, 1996;Brandt et al, 1998) but was not described for auditory (Benedict et al, 1998;Pedersen et al, 2000, for review see Johnsrude et al, 2002) or visual (Kawashima et al, 1998;Bundesen et al, 2002) attentional processing in pharmacologically unaffected healthy subjects. In this context, the finding of a focal activation of the anterior cingulate during influx vs elimination seems remarkable because the anterior cingulate is considered to have a relevant role for attentional processes in principle and is thought to encode in particular for selective attention ('selection for attention') (Demonet et al, 1993;Benedict et al, 1998).…”
Section: Attentional Performance and Neuronal Activitysupporting
confidence: 57%
See 1 more Smart Citation
“…Under alcohol induced perceptional changes, a reciprocal inhibitory auditory-visual interaction may provide a successful way to shift the dominant sensorial weight from one modality to the other as a compensatory mechanism. A similar inverse functional correlation in sensory activations could be shown for visual-vestibular stimulations of subjects without pharmacological challenge (Wenzel et al, 1996;Brandt et al, 1998) but was not described for auditory (Benedict et al, 1998;Pedersen et al, 2000, for review see Johnsrude et al, 2002) or visual (Kawashima et al, 1998;Bundesen et al, 2002) attentional processing in pharmacologically unaffected healthy subjects. In this context, the finding of a focal activation of the anterior cingulate during influx vs elimination seems remarkable because the anterior cingulate is considered to have a relevant role for attentional processes in principle and is thought to encode in particular for selective attention ('selection for attention') (Demonet et al, 1993;Benedict et al, 1998).…”
Section: Attentional Performance and Neuronal Activitysupporting
confidence: 57%
“…The reduced activity of primary and secondary visual cortex, which is also observed by other investigators using oral ethanol administration, might represent the neuronal correlate of the well-described clinical phenomena of a narrowing of the visual field ('tunnel view') and the elevated visual perception threshold under acute alcohol impact. It could be shown by vestibular activation studies that a reciprocal inhibitory visual-vestibular interaction might protect visual perception from vestibular mismatches (Brandt et al, 1998). Therefore, further functional imaging studies on the role of alcohol-induced vestibular-visual correlations are mandatory to elucidate this aspect.…”
Section: Brain Metabolic Ethanol Effectsmentioning
confidence: 99%
“…However, in this case the perception of the visual stimulus is worse with than without vestibular stimulus: the translational component is often not (well) perceived. It is known that a strong vestibular stimulus can cause the temporary perceptual freezing of a moving visual pattern (Pavard and Berthoz, 1977;Buizza, Leger, Droulez, Berthoz, and Schmid, 1980), and recent studies found physiological evidence for reciprocal cross-modal inhibition (Wenzel, Bartenstein et al, 1996;Brandt, Bartenstein et al, 1998). Also, the vestibular stimulus we imposed can temporarily decrease the retinal flow by inducing a VOR eye movement in the same direction as the optic flow in the visual stimulus: this will strongly modify the retinal flow.…”
Section: Visuo-vest Interaction In Ego-motion Reconstructionmentioning
confidence: 86%
“…Como describen todos los autores que han estudiado el fenómeno de la circularvección, se trata de una evidente interacción visuovestibular en la cual el estímulo visual provoca una serie de variaciones posturales a través de una compleja interacción con el sistema vestibular 17 , encargado realmente de la detección de las aceleraciones. Trabajos más recientes ponen en evidencia el importante papel de la corteza cerebral en la interpretación de esta compleja ilusión de movimiento 18,19 .…”
Section: Discussionunclassified